PERBEDAAN STATUS HIPERTENSI BERDASARKAN RASIO ASUPAN KALSIUM, MAGNESIUM, SERTA AKTIVITAS FISIK PADA ORANG DEWASA - Luh Arista Krismayanti; Ni Made Dewantari; Hertog Nursanyoto (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
Hypertension is a disorder in the blood vessels that causes the supply of oxygen and nutrients to the body's tissues to be blocked. Low intake of calcium and magnesium and physical activity are factors in hypertension. The purpose of this study was to determine differences in hypertension status based on the ratio of calcium and magnesium intake and physical activity in adults in the work area of Buleleng III Health Center. This type of observational research with cross sectional design. The sample size was 40 people without hypertension and 40 people with hypertension. Using the Mann Whitney Test to analyze differences. The results obtained with hypertension status are 95% calcium intake in the low category, 92.5% consume low magnesium, 75% do not match the calcium: magnesium intake ratio, and 90% are in the low physical activity category. From the Mann Whitney Test obtained differences in hypertension status based on calcium intake (p = 0,000), magnesium (p = 0,000) and physical activity (p = 0,000), while differences in hypertension status based on calcium: magnesium intake ratio obtained p = 0.003 0.05. The conclusion of this study is that there are differences in hypertension status based on the ratio of calcium and magnesium intake and physical activity in adults in the work area of Buleleng III Health Center.Keywords: Hypertension Status, Ratio of Calcium and Magnesium Intake, Physical Activity